Interventions for necrotizing pancreatitis: summary of a multidisciplinary consensus conference - Freeman, Martin L.; Werner, Jens (Pancreas, 2012)
Pancreatic and peripancreatic necrosis may result in significant morbidity and mortality in patients with acute pancreatitis. Many recommendations have been made for management of necrotizing pancreatitis, but no published guidelines have incorporated the many recent developments in minimally invasive techniques for necrosectomy. Hence, a multidisciplinary conference was convened to develop a consensus on interventions for necrotizing pancreatitis. Participants included most international experts from multiple disciplines. The evidence for efficacy of interventions was reviewed, presentations were given by experts, and a consensus was reached on each topic. In summary, intervention is primarily indicated for infected necrosis, less often for symptomatic sterile necrosis, and should ideally be delayed as long as possible, preferably 4 weeks or longer after the onset of disease, for better demarcation and liquefaction of the necrosis. Both the step-up approach using percutaneous drainage followed by minimally invasive video-assisted retroperitoneal debridement and per-oral endoscopic necrosectomy have been shown to have superior outcomes to traditional open necrosectomy with respect to short-term and long-term morbidity and are emerging as treatments of choice. Applicability of these techniques depends on the availability of specialized expertise and a multidisciplinary team dedicated to the management of severe acute pancreatitis and its complications.
Gesehen am 30.04.2018